Therapeutic Effect of Herbal Medicinal Plants on Polycystic Ovarian Syndrome: A Review - Kumar, Vineet; Kumar, Nitesh (Asian Journal of Pharmaceutical Research and Development, 2023)
Polycystic ovarian syndrome (PCOS) problem affects mature female in entire world. Menstrual irregularity, infertility, and hirsutism symptoms are all caused by PCOS patients' altered androgen and oestrogen metabolism and secretion rates. PCOS is associated to insulin resistance, obesity, and amplified concentration of hormones found in male. Both allopathic and natural treatments can be used to treat PCOS, which is becoming more common, as well as the physical and emotional issues it is connected with. Changes in sex hormones can also contribute to the development of this disease. Asparagus racemosus, Bauhinia variegata, Nigella sativa, Vitex negundo, Cocus nucifera, and other herbal plants have bioactive compounds that are safe and efficient for treating PCOS and associated complications. This review attempts to comprehend the bioactive components of natural medicinal plants that are either utilised alone or in combination to treat this condition.